Contractor management performance evaluation model at prequalification stage. Issue 12 (15th July 2015) - Rashvand, Pooria; Majid, Muhd Zaimi Abd; Pinto, Jeffrey K.
Highlights We evaluate the contractor management capability at the prequalification stage. The evaluation model is based on the management practices. ANP was used to evaluate the multidirectional relationship among decision elements. The technicality and feasibility of the model was validated. The model enhances the decision support tools for clients.